MORPHOLOGICAL CHANGES IN THE PANCREAS IN ACUTE STRESS DEPENDING ON THE STRESS RESISTANCE OF ANIMALS AND UNDER PREVENTIVE MELANIN INTRODUCTION - Слободяник, Н.М.; Neporada, K.S.; Nikolenko, D.Ye. (World of Medicine and Biology, 2015)
Laboratory rats were subjected to simulation of acute stress to clear out stress-protective effect produced by melanin on the development of pathological changes in the pancreas depending on the stress resistance of the animals. Histological specimen of pancreatic tissues taken from stress-susceptible rats exposed to acute immobilization stress demonstrated necrobiotic changes of diffuse character. Among the cells of islet apparatus there were some changes of morphological structure that pointed put partly reversible and irreversible destructive signs. Reactive changes to acute stress were also found out in the pancreatic stroma. However, in the affected acinar structures of the pancreas there were noticed the configurations of mitosis, indicating its regenerative activity. Reactive changes due to acute stress were also revealed in the stroma of the gland. Histological study of the pancreas in stress-susceptible rats which were administered melanin prior to modeling of acute immobilization stress shown destructive changes of microfocal character. Most of the pancreatic acini were observed to be in the condition of secretory activity. Interacinic edematous stroma was edematous and contained activated fibroblasts, arterioles were paretic expanded. In areas of pancreatic necrosis some acini had fuzzy contours of the cells, their nuclei were in lysis, cytoplasm appeared homogenized having no division of secretory compartments corresponding basophilic and eosinophilic areas. On the border between necrotic tissue and intact gland acini an increased number of mitosis was revealed, showing the activation of reparative tissue regeneration. Stress-resistant rats when being exposed to acute immobilization stress showed no diffuse destruction of pancreatic tissue. No destructive changes were found in the islet apparatus, deterioration of blood flow detected was minimal. Histological sections of pancreatic tissue of stress-resistant rats, which were administered melanin prior to acute stress showed increased synthetic activity of acinic cells and their proliferation in some areas. Islet apparatus in this case demonstrated no destructive changes. Stress-susceptible animals were observed to have more marked signs of tissue necrosis and pancreatic microcirculatory disorders compare with stress-resistant animals under the conditions of acute immobilization stress. Melanin administration prior the simulation of acute stress produced stress-protective properties, which were manifested by high regenerative activity of secretory cells, improved hemodynamics and by the decrease of necrotic changes of pancreas.